Aghradu al-Saja’ fi al-Qur’an al-Karim (Dirasah Tahliliyah Badi’iyyah fi Surati al-Muzzammil) - Maula, Inayatul; Nurawaliyah, Pina (Department of Arabic Teaching, STAI PUI Majalengka, 2025)
This research includes a study of Badi’iyyah studies which is one of the types of studies in the ilm al-Balaghah. Ilm al-Badi’ is concerned with improving speech in terms of expression and meaning. One of the elements within the field of